Effect of respiration on cardiac filling at rest and during exercise in Fontan patients: A clinical and computational modeling study. (7th December 2015) - Van De Bruaene, Alexander; Claessen, Guido; La Gerche, Andre; Kung, Ethan; Marsden, Alison; De Meester, Pieter; Devroe, Sarah; Bogaert, Jan; Claus, Piet; Heidbuchel, Hein; Budts, Werner; Gewillig, Marc
Abstract: Background: Due to the absence of a sub-pulmonary ventricle, the Fontan circulation is sensitive to respiration-induced changes in intrathoracic pressure. However, the importance of a 'respiratory pump' in creating forward flow remains controversial. We aimed at evaluating the effect of respiration on ventricular filling during exercise using clinical data and computational modeling predictions. Methods: Ten Fontan patients (6 male, 20 ± 4 years) underwent ungated cardiac magnetic resonance (CMR) imaging at rest and during supine bicycle exercise to evaluate systemic ventricular volumes (end-diastolic volume index (EDVi), end-systolic volume index (ESVi) and stroke volume index (SVi)) during normal respiration and a Valsalva maneuver. Respiratory-dependent SV was calculated. Clinical results were compared to predictions made by a closed-loop lumped-parameter (LPN) computational model of Fontan circulation. Results: Inspiration resulted in increased EDVi (98 ± 16 to 103 ± 15 mL; P = 0.001), SVi (55 ± 9 to 59 ± 9 mL; P = 0.001) and cardiac index (3.9 ± 0.7 to 4.2 ± 0.8 L/min; P = 0.002), whereas ESVi (P = 0.096) remained unchanged. The effect of inspiration on EDVi (mean effect + 6 ± 1 mL; P < 0.0001) and SVi (+ 4 ± 1 mL; P < 0.0001) was maintained during exercise. Respiratory-dependent SVi tended to increase during exercise (3 ± 2% to 5 ± 3%; P = 0.084). Valsalva resulted in decreased EDVi (P = 0.001), ESVi (P = 0.003) and SVi (P = 0.005). Computational modeling indicated higher EDV and SV at end-inspiration and expiration, showing a phased time delay between peak caval vein flow and peak SV. Conclusion: In Fontan patients, inspiration resulted in increased ventricular filling at rest and during exercise. Results were confirmed using a computational model indicating a phased time delay between peak SV and peak caval vein flow.